A novel near-infrared turn-on and ratiometric fluorescent probe capable of copper(ii) ion determination in living cells. Issue 45 (19th May 2020) - Aydin, Ziya; Yan, Bing; Wei, Yibin; Guo, Maolin
Abstract : A novel NIR ratiometric fluorescent probe has been developed for monitoring the dynamic changes of subcellular Cu 2+ and quantifying its concentration at the nanomolar level in living cells. Abstract : A near-infrared ratiometric fluorescent probe CR-Ac based on a coumarin–benzopyrylium platform has been developed for selective detection of Cu 2+ . The cell imaging data revealed the capabilities of CR-Ac in monitoring the dynamic changes of subcellular Cu 2+ and the quantification of Cu 2+ levels in living cells.